Feasibility Study on Application of Radio Frequency Identification (RFID) in Railway Wheel Monitoring System - Gana Selvan, Navin Raj; Ramli, Mimi Faisyalini; Zulkepli, Zariq Zdoeriev Zuklivly (Progress in Engineering Application and Technology, 2022)
In practise, most of the railway wheel monitoring activity in Malaysia is being done manually such as using underfloor wheel lathe(UWFL) and dial gauge. The process of manual monitoring is time consuming, requires more manpower and with higher tendency of error during the transportation of data. Therefore, to improve the process, this project proposes RFID based system for the wheel monitoring, as it could increase the effeciency of the process as the data can be delivered directly to the Operation Control Centre (OCC). Matlab Simulink was used to guarantee that the design of the simulation is feasible. The final result for this simulation is based on the data of the output spectrum analyzer. By using Kurtosis method, it is possible to detect the condition of the railway wheel whether in healthy or damaged. Overall, application of RFID in railway wheel monitoring system enhanced the effectiveness of railway wheel maintenance operation.